2021
DOI: 10.3389/fimmu.2021.621754
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of a 4-Component Toxoid-Based Staphylococcus aureus Vaccine in Rhesus Macaques

Abstract: Staphylococcus aureus is a leading cause of significant morbidity and mortality and an enormous economic burden to public health worldwide. Infections caused by methicillin-resistant S. aureus (MRSA) pose a major threat as MRSA strains are becoming increasingly prevalent and multi-drug resistant. To this date, vaccines targeting surface-bound antigens demonstrated promising results in preclinical testing but have failed in clinical trials. S. aureus pathogenesis is in large part driven by immune destructive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…Hla toxoid harbors two mutations (H35L and H48L), PVL toxoid consists of mutated S and F subunit proteins (LukS mut9 and LukF mut1 ), a dimeric toxoid LukAB mut50 , and a fusion protein TBA 225 , which represents three superantigen toxoids fused together via a flexible linker (TSST-1, SEB and SEA). Each of these toxoids is fully attenuated, and the safety and immunogenicity had been extensively studied previously ( 40 ). Using five toxoid proteins blended at equal weight ratios as immunogen to immunize rabbits, strong antibody responses were elicited.…”
Section: Resultsmentioning
confidence: 99%
“…Hla toxoid harbors two mutations (H35L and H48L), PVL toxoid consists of mutated S and F subunit proteins (LukS mut9 and LukF mut1 ), a dimeric toxoid LukAB mut50 , and a fusion protein TBA 225 , which represents three superantigen toxoids fused together via a flexible linker (TSST-1, SEB and SEA). Each of these toxoids is fully attenuated, and the safety and immunogenicity had been extensively studied previously ( 40 ). Using five toxoid proteins blended at equal weight ratios as immunogen to immunize rabbits, strong antibody responses were elicited.…”
Section: Resultsmentioning
confidence: 99%
“…The current paradigm for vaccine development is targeting multiple staphylococcal virulence factors, considering both the surface antigens and secreted biologically active substances. Thus S. aureus adhesins and other surface proteins will generate opsonic antibodies, while non-toxic forms of toxins and superantigens will stimulate the production of neutralizing antibodies and activate effector immune cells [93,94]. An example of such a complex preparation is the S. aureus toxoid vaccine, containing modified bi-component pore-forming toxins: mutants of the S and F subunits of PVL (LukS mut9 and LukF mut1 ) and a double mutant of alpha hemolysin (Hla H35L/H48L ), as well as the fusion toxoid TBA 225 of superantigens (SEA, SEB and TSST-1).…”
Section: Past and Present In Active And Passive Immunotherapy Of Stap...mentioning
confidence: 99%
“…Moreover, the population of antigenspecific T cells of the Th1 and Th17 phenotype, as well as the production of some T cell cytokines (e.g., TNF, IFN-γ, IL-2, IL-17A), increased in response to ex vivo re-stimulation of peripheral blood mononuclear cells with the vaccine. It is suggested that such a T cell response may, via feedback, activate the innate immune cells that enhance phagocytosis and bacteria elimination [94].…”
Section: Past and Present In Active And Passive Immunotherapy Of Stap...mentioning
confidence: 99%
“…Notably, rabbits, while still much less than that of humans, are more susceptible to the effect of many S. aureus toxins, therefore suggesting rabbits as a more relevant in vivo model ( 106 ). S. aureus vaccines and monoclonal antibodies have also occasionally been tested in non-human primates, generating highly relevant data ( 107 , 108 ).…”
Section: Models For the Study Of S Aureus Infectionsmentioning
confidence: 99%